Identification of potential bioactive phytochemicals for the inhibition of platelet-derived growth factor receptor β: a structure-based approach for cancer therapy - Habib, Insan; Sulaimani, Md Nayab; Jairajpuri, Deeba Shamim; Hussain, Afzal; Mohammad, Taj; Alajmi, Mohamed F.; Shamsi, Anas; Hassan, Md Imtaiyaz (Frontiers in Molecular Biosciences, 2024)
Platelet-derived growth factor receptor beta (PDGFRβ) belongs to the receptor tyrosine kinase (RTK) protein family and is implicated in several disorders such as hematopoietic, glial, and soft-tissue cancer, non-cancerous disorders, including skeletal defects, brain calcification, and vascular anomalies. The research on small molecule inhibitors targeting PDGFRβ in cancer treatment has seen promising developments, but significant gaps remain. PDGFRβ, receptor tyrosine kinase, is overexpressed in various cancers and plays an important role in tumor progression, making it a potential therapeutic target. However, despite advances in identifying and characterizing PDGFRβ inhibitors, few have progressed to clinical trials, and the mechanistic details of PDGFRβ's interactions with small molecule inhibitors are still not fully understood.Moreover, the specificity and selectivity of these inhibitors remain challenging, as off-target effects can lead to unwanted toxicity. In this investigation, two compounds, Genostrychnine and Chelidonine, were discovered that help stimulate the kinase activity PDGFRβ. These small molecules were identified by employing various parameters involved in the drug discovery process, such as Lipinski's rule of five (RO5), 2D similarity search and 3D pharmacophorebased virtual screening followed by MD simulation studies. The identified molecules were found to be very effective and significantly stimulated the PDGFRβ activity. Overall, our findings demonstrate that these small drug-like compounds can be beneficial tools in studying the properties of PDGFRβ and can play a crucial role in the therapeutic development of cancers and other associated diseases.